Prototipe Ibu Ideal: Kajian Linguistik Kognitif - Millatuz Zakiyah (BUANA GENDER : Jurnal Studi Gender dan Anak, 2018)
This study discusses the ideal mother prototype in Indonesian cognition. This study discusses about what is the ideal mother prototype variable that is most influential in the cognition of Indonesian people and how does the background influence of respondents to the ideal mother prototype. This study uses the prototype theory of Tomaszczyk (2007) in cognitive linguistic studies. This study used variables housewife/stay at home mom; parenting; and doing their own household work, such as sweeping, to measure mother ideality. The results indicated that the prototype variables of the most influential ideal mother were Â parenting their own children; do their own household work; and Â housewife/stay at home mom. Meanwhile, based on the gender background of the respondents, both male and female respondents considered "parenting" as the most influential variable. However, in the second rank, men consider the variable "housewife/stay at home mom" more influential than "doing their own household work ", while female respondents, on the contrary. Meanwhile, based on the background of the respondent's marriage, both respondents who have and have not married there is no difference, the variable "parenting" is the most influential variable, then "doing their own household work" and "housewife/stay at home mom".